From Incidentaloma to Suspicion of Malignancy: The Diverse Clinical Presentation of Gonadal Schistosomiasis mansoni. (10th December 2013) - Almeida, Laiana do Carmo; de Oliveira, Marbele Guimarães; Castro Pereira, Fábio Meira; de Bessa Júnior, José
Abstract : Schistosomiasis is the second most widespread parasitic disease in the world, second only to malaria. The usual places the Schistosoma mansoni can be found in are the rectal and sigmoidal venules, as well as other segments of the large intestine of men. It may also be present in other ectopic topographies. Gonadal schistosomiasis is an unusual presentation of Schistosomiasis mansoni and its different clinical signs and symptoms disrupt correct diagnosis and culminate in surgical treatment that is, in most cases, unnecessary. In this study, we report four cases of gonadal Schistosomiasis mansoni, two in the ovary and two in the testicles. These cases were clinically investigated as a bacterial infection, a benign neoplasm, and a suspected cancer, whilst one of them was an incidentaloma.